2011
DOI: 10.1245/s10434-011-1982-y
|View full text |Cite
|
Sign up to set email alerts
|

Volume of Excision and Cosmesis with Routine Cavity Shave Margins Technique

Abstract: CSM decreases the need for re-excision. Total tissue volume excised is lower in patients who undergo CSM, and cosmetic results appear to be improved. This approach should be considered for all patients undergoing PM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 18 publications
2
21
2
4
Order By: Relevance
“…15 However, Mook et al, in a retrospective study, found that cavity shaving was associated with a smaller volume of excised tissue than was standard partial mastectomy (80.7 cm3 versus 165.1 cm3), which raises the possibility that surgeons who perform cavity shaving routinely excise less tissue initially and excise excess tissue during shaving. 13 Positive margin in our study before shave was in 40% but after shaving it was in only 10% of shave group, however in non-shave group it was in 35% of patients. Several retrospective studies have shown similar findings.…”
Section: Demographic and Clinical Patients' Data (Table)contrasting
confidence: 48%
See 1 more Smart Citation
“…15 However, Mook et al, in a retrospective study, found that cavity shaving was associated with a smaller volume of excised tissue than was standard partial mastectomy (80.7 cm3 versus 165.1 cm3), which raises the possibility that surgeons who perform cavity shaving routinely excise less tissue initially and excise excess tissue during shaving. 13 Positive margin in our study before shave was in 40% but after shaving it was in only 10% of shave group, however in non-shave group it was in 35% of patients. Several retrospective studies have shown similar findings.…”
Section: Demographic and Clinical Patients' Data (Table)contrasting
confidence: 48%
“…However, others claimed that it is sufficient to excise selective margins where the tumor appears to be close to the edge of the specimen on the basis of intraoperative imaging and gross assessment. [7][8][9][10] The tumor edges differ from patient to patients and can be summarized in the following types: [11][12][13] • Positive edges: tumor cells are present at the edge In all studies, the highest local reoccurrence rate corresponds to "more than focally positive margins" and lowest local recurrences rate to "negative margin tumors".…”
Section: Introductionmentioning
confidence: 99%
“…Systematic cavity shaving has been shown to be a feasible and low morbidity procedure 17 . Mook et al demonstrated, in a retrospective study, that serial enlargement of the margins allows the surgeon to remove a smaller amount of breast tissue, preventing oncological damages and gaining considerable cosmetic benefits 18 . In the present study, the benefit of the described technique was noteworthy, and reoperation was avoided in 18 patients from the total number of operated cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have suggested that CSM not only halves the rate of re-excision but also improves cosmetic results [4,14]. Chapgar et al (2015) found that the volume of tissue excised in the CSM group was directly proportional to the volume of tissue [3].…”
Section: Discussionmentioning
confidence: 99%